MET Y1003S point mutation shows sensitivity to crizotinib in a patient with lung adenocarcinoma. (April 2019) - Miao, Yun L.; Xu, Qing Qing
Highlights: MET Y1003S is a unique subset of MET exon 14 alterations that does not affect splicing. Y1003S mutations can lead to decreased MET degradation, increased oncogenic signaling. The patient with Y1003S mutation got tumor remission after crizotinib treatment. The response to crizotinib in our case was both rapid and durable. Abstract: Objectives: MET amplification or MET exon 14 skipping site mutation can be treated with crizotinib in non-small cell lung cancer patients. Y1003 is a binding site for E3 ubiquitin ligase, which is critical for MET degradation. Here we show an adenocarcinoma patient with Y1003S mutation and she got tumor remission after crizotinib treatment. Materials and methods: A 61-year-old never-smoking female was admitted to our hospital due to increased carcino-embryonicantigen. Positron emission tomography (PET)-CT showed enlargement of bilateral cervical, left supraclavicular and multiple mediastinal lymph nodes. PET-CT also showed stripe in the left upper lobe. Adenocarcinoma cells were found from biopsy on her left supraclavicular lymph nodes. We detected cell-free circulating tumor DNA (ctDNA) from peripheral blood and identified a MET Y1003S mutation by next generation sequencing technology. Y1003 mutations predicted to be similar to MET exon 14 skipping in functionality based on the literature. After an extensive discussion of treatment options, the patient opted to treatment with crizotinib, a small-molecule dual inhibitor of the MET and ALK. Results and conclusion: Dramatic response was observed within 1 months of treatment, which lasted more than 10 months. Chest CT scans revealed significant improvement of the lung focus and decrease in size of the lymph nodes lesions, meeting RECIST partial response criteria (−30%). Y1003 alterations may be diverse mutations and sensitive to MET inhibitors.